A heavy metal baseline score predicts outcome in acute myeloid leukemia. Issue 4 (4th March 2020) - Ohanian, Maro; Telouk, Philippe; Kornblau, Steven; Albarede, Francis; Ruvolo, Peter; Tidwell, Rebecca S. S.; Plesa, Adriana; Kanagal‐Shamanna, Rashmi; Matera, Eva‐Laure; Cortes, Jorge; Carson, Arch; Dumontet, Charles
Abstract: Despite abundant epidemiological data linking metals to leukemia and other cancers, baseline values of toxic and essential metals in patients with leukemia and the clinical impact of these metals remain unknown. Thus, we sought to quantify metal values in untreated patients with acute myeloid leukemia (AML) and controls and determine the impact of metal values on AML patients' survival. Serum samples from patients with untreated AML and controls at Hospices Civils de Lyon were analyzed and compared for trace metals and copper isotopic abundance ratios with inductively coupled plasma mass spectrometry. Survival analysis was performed as a function of metal values, and a multi‐metal score was developed for patients with AML. Serum samples were collected from 67 patients with untreated AML and 94 controls. Most patients had intermediate‐risk cytogenetics (63.1%) without FLT 3 internal tandem duplication mutations (75.6%) or NPM1 mutations (68.1%). Most metal values differed significantly between AML and control groups. Patients with lower magnesium and higher cadmium values had the worst survival rates, with only 36% surviving at 6 months ( P = .001). The adverse prognostic effect of this combination was maintained on multivariate analysis. Based on this, we developed a novel metal score, which accounts for multiple relative abnormalities in the values of five toxic and five essential metals. Patients with a higher metal score had significantly worse survival, which was maintained on multivariate analysis ( P = .03). This baseline metal scoring system was also prognostic when we applied it to a separate population of front‐line AML patients.